Enhancing TB Vaccine Efficacy: Current Progress on Vaccines, Adjuvants and Immunization Strategies - Hui Wang; Shuxian Wang; Ren Fang; Xiaotian Li; Jiayin Xing; Zhaoli Li; Ningning Song (Vaccines, 2023)
Tuberculosis (TB) remains a global infectious disease primarily transmitted via respiratory tract infection. Presently, vaccination stands as the primary method for TB prevention, predominantly reliant on the Bacillus Calmette–Guérin (BCG) vaccine. Although it is effective in preventing disseminated diseases in children, its impact on adults is limited. To broaden vaccine protection, efforts are underway to accelerate the development of new TB vaccines. However, challenges arise due to the limited immunogenicity and safety of these vaccines, necessitating adjuvants to bolster their ability to elicit a robust immune response for improved and safer immunization. These adjuvants function by augmenting cellular and humoral immunity against M. tuberculosis antigens via different delivery systems, ultimately enhancing vaccine efficacy. Therefore, this paper reviews and summarizes the current research progress on M. tuberculosis vaccines and their associated adjuvants, aiming to provide a valuable reference for the development of novel TB vaccines and the screening of adjuvants.